2008
DOI: 10.1155/2008/564561
|View full text |Cite
|
Sign up to set email alerts
|

Visual Scanning and Reading Ability in Normal and Dyslexic Children

Abstract: Very few studies have investigated the development of visual search of aligned stimuli in relation to normal reading acquisition and in developmental dyslexia. In this study we used a new computerised experimental task which requires a visuo-motor response (RT) to a target appearing unpredictably in one out of seven different spatial positions on a horizontally aligned array of 18 geometrical figures.The aims of the study were to investigate: (1) the visual scanning development in normal children from pre-scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 14 publications
2
42
0
1
Order By: Relevance
“…These results are consistent with recent predictive and longitudinal studies that suggest a specific role of magnocellular-dorsal as well as visual spatial attentional systems during the development of early reading abilities (e.g. Boets et al, 2008;Ferretti et al, 2008;Kevan & Pammer, 2008, 2009Plaza & Cohen, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with recent predictive and longitudinal studies that suggest a specific role of magnocellular-dorsal as well as visual spatial attentional systems during the development of early reading abilities (e.g. Boets et al, 2008;Ferretti et al, 2008;Kevan & Pammer, 2008, 2009Plaza & Cohen, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, recent longitudinal studies have suggested that magnocellular-dorsal stream sensitivity and attentional processing, in addition to phonological awareness, is an important predictor of early reading abilities (e.g. Boets, Wouters, van Wieringen, De Smedt, & Ghesquière, 2008;Ferretti, Mazzotti, & Brizzolara, 2008;Kevan & Pammer, 2009;Plaza & Cohen, 2006).…”
Section: Introduction Dmentioning
confidence: 99%
“…To this aim, it is worth noting that the reading performance of dyslexic children has been shown to improve following a specific training for visuospatial attention (e.g., Facoetti, Lorusso, Paganoni, Umiltà, & Mascetti, 2003;Geiger, Lettvin, & Fanhle, 1994). Moreover, longitudinal studies have shown that visual attention, in addition to syllable awareness, is one of the most important predictors of early reading abilities (e.g., Ferretti, Mazzotti, & Brizzolara, 2008;Plaza & Cohen, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although this fact has been known for more than 20 years, little is known about the causalities here: do these abnormal gaze patterns lead to dyslexic reading, or are they a consequence of reading difficulties potentially reflecting compensatory mechanisms? In order to address this question, a non-lexical and non-orthographical reading paradigm was developed (Corbic et al, 2007; Günther et al, 2012b; for the earlier work using the “Z-reading paradigm” see Ferretti et al, 2008). This “Landolt” paradigm allows investigating eye movements during reading without any influence of lexical information such as lexical frequency, phonotactics, or lexical status (Zschornak and Zeschmann, 2008; available at http://www.tguenthert.de/thesis/files/archive-2008.html; Zschornak et al, 2012; available at https://www.thieme-connect.de/ejournals/html/10.1055/s-0032-1304900).…”
Section: Introductionmentioning
confidence: 99%